1996
DOI: 10.1590/s0036-46651996000500007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non-specific immunopotentiators in experimental Schistosoma mansoni infection: II. Corynebacterium parvum

Abstract: The effects of Corynebacterium parvum on host protection, tissue reaction and "in vivo" chemotaxis in Schistosoma mansoni infected mice were studied. The C. parvum was given intraperitoneally using a dose of 0.7 mg, twice a week (for 4 weeks), thirty days before (prophylactic treatment) or after infection (curative treatment). The host protection was evaluated through the recovery of adult worms by liver perfusion and was lower in the prophylactic group as compared to the control group (p = 0.018), resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…It is well known that the treatment of animals with killed P. acnes increases lymphocyte population such as B lymphocytes, TCD4 + , TCD8 + and NKT cells, and potentiates their functions (13,24,26). The increase on animal resistance to several infections was also observed after killed P. acnes animal treatment (27–31).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…It is well known that the treatment of animals with killed P. acnes increases lymphocyte population such as B lymphocytes, TCD4 + , TCD8 + and NKT cells, and potentiates their functions (13,24,26). The increase on animal resistance to several infections was also observed after killed P. acnes animal treatment (27–31).…”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, several clinical and experimental studies in vivo and in vitro reported the effects of killed Propionibacterium acnes suspension on innate and adaptive immune response modulation. Among these, it was observed increase on the phagocytic and tumoricidal macrophages activities (21–24), adjuvant effect in the antibody response (25,26) and augmentation of the animal resistance to different types of pathogens (27–31).…”
Section: Introductionmentioning
confidence: 99%
“…When such bacterial suspension is administered to human and experimental animals, it induces biological effects that modulate the innate and acquired immune responses. One of the most important P. acnes adjuvant effects is the increase in macrophage phagocytic activity [1,2], which can explain, in part, the bacterium ability to enhance animal resistance to several pathogens [3][4][5][6][7][8][9]. It also enhances a tumoricidal macrophage activity, as demonstrated in several experimental and clinical studies [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been extensively studied for its immunomodulatory effects when administered as killed bacteria in experimental models. Killed P. acnes increases lipopolysaccharide (LPS)-induced endotoxic shock (Green et al, 1977), activates the mononuclear phagocytic system (Halpern et al, 1963), induces tumoricidal activity Halpern et al, 1966;Woodruff et al, 1974), acts as adjuvant for antibody response Warr and James, 1975) and enhances resistance to infections (Abath et al, 1988;Brener and Cardoso, 1976;Ha et al, 1986;Hill, 1987;Nussenzweig, 1967;Squaiella et al, 2001;Teixeira et al, 1996).…”
Section: Introductionmentioning
confidence: 99%